Is Biomedical Research Protected from Predatory Reviewers? - Al-Khatib, Aceil; Teixeira da Silva, Jaime A. (Science & Engineering Ethics, 2019)
Authors endure considerable hardship carrying out biomedical research, from generating ideas to completing their manuscripts and submitting their findings and data (as is increasingly required) to a journal. When researchers submit to journals, they entrust their findings and ideas to editors and peer reviewers who are expected to respect the confidentiality of peer review. Inherent trust in peer review is built on the ethical conduct of authors, editors and reviewers, and on the respect of this confidentiality. If such confidentiality is breached by unethical reviewers who might steal or plagiarize the authors' ideas, researchers will lose trust in peer review and may resist submitting their findings to that journal. Science loses as a result, scientific and medical advances slow down, knowledge may become scarce, and it is unlikely that increasing bias in the literature will be detected or eliminated. In such a climate, society will ultimately be deprived from scientific and medical advances. Despite a rise in documented cases of abused peer review, there is still a relative lack of qualitative and quantitative studies on reviewer-related misconduct, most likely because evidence is difficult to come by. Our paper presents an assessment of editors' and reviewers' responsibilities in preserving the confidentiality of manuscripts during the peer review process, in response to a 2016 case of intellectual property theft by a reviewer. Our main objectives are to propose additional measures that would offer protection of authors' intellectual ideas from predatory reviewers, and increase researchers' awareness of the responsible reviewing of journal articles and reporting of biomedical research.